2012
DOI: 10.1097/shk.0b013e31825e2a85
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width Is an Independent Predictor of Mortality in Patients With Gram-Negative Bacteremia

Abstract: Red blood cell distribution width (RDW) is known to be a predictor of severe morbidity and mortality in some chronic diseases such as congestive heart failure. However, to our knowledge, little is known about RDW as a predictor of mortality in patients with Gram-negative bacteremia, a major nosocomial cause of intra-abdominal infections, urinary tract infections, and primary bacteremia. Therefore, we investigated whether RDW is an independent predictor of mortality in patients with Gram-negative bacteremia. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
112
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 34 publications
5
112
1
2
Order By: Relevance
“…A study by Guclu et al (21) found that the AUC of PDW was 0.733 (95% CI: 0.678-0.783) with a sensitivity of 59.31% and a specificity of 76.22%. An investigation by Ku et al (4) observed that the AUC of RDW was 0.764 (95% CI: 0.650-0.879). Therefore, the two indices PDW and RDW have diagnostic power in the discrimination of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Guclu et al (21) found that the AUC of PDW was 0.733 (95% CI: 0.678-0.783) with a sensitivity of 59.31% and a specificity of 76.22%. An investigation by Ku et al (4) observed that the AUC of RDW was 0.764 (95% CI: 0.650-0.879). Therefore, the two indices PDW and RDW have diagnostic power in the discrimination of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…PDW is measure of variation in platelet size, which may be an indicator of active platelet release (3). A number of previous investigations have shown that RDW and PDW are significantly associated diseases including chronic spontaneous urticaria and gram-negative bacteremia (3)(4)(5). Furthermore, RDW has also been regarded as a prognostic marker for certain diseases, such as stable angina pectoris (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It was used in the distinctive diagnosis of anaemia for years [13]. Studies investigating the relationship between RDW and cardiovascular diseases, inflammatory diseases and DM were made recently.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW on complete blood count reflects impairment in erythropoiesis and abnormal red blood cell survival which can be caused by any disease involving red blood cell destruction or production [1]. In recent years, several studies have demonstrated that elevation of this simple parameter is associated with increased risk of mortality in different contexts including sepsis, cardiovascular disease, cancer, and chronic lower respiratory tract disease [2][3][4][5][6][7][8][9][10]. It is established that inflammation and oxidative stress affect RDW and it has been shown that RDW elevation is associated with raise in the cytokines such as IL6, TNF-α [11,12].…”
Section: Introductionmentioning
confidence: 99%